2003
DOI: 10.1093/bja/aeg077
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of ropivacaine 0.5% (in glucose 5%) with bupivacaine 0.5% (in glucose 8%) for spinal anaesthesia for elective surgery †

Abstract: Ropivacaine 15 mg in glucose 50 mg ml(-1) provides reliable spinal anaesthesia of shorter duration and with less hypotension than bupivacaine. The recovery profile for ropivacaine may be of interest given that more surgery is being performed in the day-case setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
77
4
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(111 citation statements)
references
References 14 publications
19
77
4
5
Order By: Relevance
“…Difference in the onset of motor blockade in both groups was also found to be statistically significant (P <0.05). These findings of present study are similar with the findings stated by Van [17][18][19][20][21][22] The duration of sensory blockade was defined as time elapsed between injection of study drug and return of the pin prick sensation whereas duration of motor blockade was defined as time between drug injections to complete return of motor power with movement of all lower limb joints. It was found that longer duration of sensory and motor blockade in bupivacaine group as against in ropivacaine group and difference was statistically significant (P <0.05).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Difference in the onset of motor blockade in both groups was also found to be statistically significant (P <0.05). These findings of present study are similar with the findings stated by Van [17][18][19][20][21][22] The duration of sensory blockade was defined as time elapsed between injection of study drug and return of the pin prick sensation whereas duration of motor blockade was defined as time between drug injections to complete return of motor power with movement of all lower limb joints. It was found that longer duration of sensory and motor blockade in bupivacaine group as against in ropivacaine group and difference was statistically significant (P <0.05).…”
Section: Discussionsupporting
confidence: 91%
“…However, in other studies no significant defference was foud in haemodynamics in both ropivacaine and bupivacaine groups when given intrathecally. [18][19][20][23][24][25] In present study no rescue analgesia was required in any of the patients in any group and quality of anesthesia obtained was adequate with both the groups. No signs of central nervous system toxicity (like restlessness, anxiety, incoherent speech, lightheadedness, dizziness, blurred vision, tremors, drowsiness, convulsions) or cardiovascular system toxicity (hypotension, bradycardia, hypertension, tachycardia, vasovagal reaction, arrhythmias like extra-systoles, atrial fibrillation, ST segment changes and myocardial infarction); severe allergic reactions (rash, itching, difficulty in breathing, tightness in the chest, swelling of the mouth, face, lips or tongue); nausea; vomiting noted in both groups.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…18 Whiteside et al who found the time to maximum degree of motor block in bupivacaine was significantly less (P<0.001) than ropivacaine group whereas Chung et al found that the both drugs ropivacaine and bupivacaine took similar time to complete motor block. 17,19 In present study in Group R motor block onset time is significantly higher (P=0.030) than Group L. In our study duration of sensory block and motor block is significantly more in Group L than Group R (P=0.037). Breebart et al compared 10 mg levobupivacaine and 15 mg ropivacaine for out patients knee arthroscopy and found the same results, where ropivacaine group moved early and need for postoperative analgesia was less in levobupivacaine but they discharged home late.…”
Section: L3supporting
confidence: 44%